Heart to Heart: From Nuclear Proteins to Emery-Dreifuss Muscular Dystrophy - Morris, Glenn E.; Manilal, Sushila (Human molecular genetics, 1999)
Emery-Dreifuss muscular dystrophy has some remarkably specific features, with only cardiac and skeletal tissues being affected. Equally remarkably, the disease is caused by mutations in widely expressed genes for the nuclear membrane/lamina proteins, emerin and lamin A/C. How do mutations in proteins at the heart of the cell lead to stiff joints and sudden heart failure? This and related questions are the subject of this review.